2020
DOI: 10.3390/healthcare9010028
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Symptom Groups and Functioning Domains in Patients with Advanced-Stage Non-Small Cell Lung Cancer Undergoing Treatment: A Cross-Sectional Study

Abstract: The purpose of this study was to describe the symptoms experienced by patients with non-small cell lung cancer (NSCLC), examine whether different symptom groups significantly affected different functioning domains in these patients, and determine the effect of the “lack of energy” and “pain” symptom groups on the different functioning domains of health-related quality of life (HRQOL). From a single tertiary institution, this cross-sectional study enrolled 135 consecutive NSCLC patients who were mostly undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The 17 experts are all women, with an average of 19.71 years of work experience. Among the 17 intervention measures constitute the main content of the second round of Delphi. The statistical results of 17 expert evaluations are shown in Table 4.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 17 experts are all women, with an average of 19.71 years of work experience. Among the 17 intervention measures constitute the main content of the second round of Delphi. The statistical results of 17 expert evaluations are shown in Table 4.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The symptom cluster was proposed in 2002 by American scholar Dodd [15] et al, which initially refers to the simultaneous occurrence of three or more interrelated symptoms, and was later rede ned by Kim[16] et al It refers to the simultaneous occurrence of two or more interrelated symptoms, which are synergistic and mutually reinforcing, and have a far greater impact than a single symptom. The symptom cluster affects patients' prognosis, quality of life, and functional status, leading to serious physiological, psychological, and economic burdens, and even delay or discontinue treatment [17,18]. Patients with lung cancer undergoing chemotherapy have a variety of symptom clusters [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A previous qualitative study reported that dyspnea played a primary role in the onset of fatigue in patients with LC. Pain in patients with LC may be caused by the tumor itself, treatment, diagnostic tests, surgeries, procedures (e.g., biopsy, puncture, mediastinoscopy, thoracotomy), local or metastatic invasion of a tumor into the chest with consequent inflammation or pulmonary embolism of the invaded area, or due to tumoral compression of bones, nerves, or other organs [6]. Although there are numerous signaling pathways, including the MAPK, PI3K, oxidative stress response, RNA splicing, processing, and nucleosome remodeling pathways, have been linked to causal gene changes [7].…”
Section: Lung Cancermentioning
confidence: 99%
“…Fig 6. Deacetylation Mechanism of SIRT3 by nicotinamide adenine dinucleotide on several Lys residues in SDHA of mitochondria Complex ΙΙ[83] …”
mentioning
confidence: 99%